The evolution of Information and Communication Technologies from the perspective of Touraine, Bell and Castells (Research, Society and Development, 2019)
This paper aims to make a historical rescue of the transformations that have occurred over time with regard to Information and Communication Technologies, ICTs, and how they imply in the life of the subjects of working origin. In this way, the communication and the development of the media by the human being, from their efforts, that have led to the development of the technologies of communication and information, the ICTs. For this discussion, authors of the discussion about technology and society, such as Alain Touraine (1971), who brings the theory of the "Scheduled Society", as well as Manuel Castells (1999), were used. brings the "Society in network". In addition to these authors, we highlight the studies of Daniel Bell (1973), which fosters discussions about the "post-industrial society". The choice of these authors was initially due to their relevance to the issues that deal with society and its relationship with technology. It is concluded that for this "flexible" labor force, prior qualification matters less than the adaptability, which includes both cognitive, practical or behavioral skills, as well as the competence to learn and to submit to the new. The consequences of today's computer-based society and the flexibility of markets are seen in a very negative way, among other things that bring damage to growing portions of the population, especially with the changes in the labor market that exploit and mutilate capacities physical and intellectual.